Pengaruh Pengalaman Kerja, Pendidikan dan Independensi Auditor Terhadap Kualitas Audit - Kristianto, Eldi Januari; Pangaribuan, Hisar (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the effect of work experience, education level, and also auditor independence on the quality of audit results. The data in this study are auditors who work in public accounting firms that have been registered at the Indonesian Institute of Certified Public Accountants (IAPI). The sample used in this study were 137 respondents from 11 accounting firms. This data is primary data obtained through the distribution of questionnaires. The sampling technique uses purposive sampling, while the data processing method uses multiple linear analysis using SPSS windows version 25. The results of this study indicate that work experience, level of education and auditor independence partially affect the quality of audit results